The Influence Of Transformational Leadership And Self Efficacy On Employee Performance At The Regional Secretariat Of Lebong District - Bugianto, Hendri; Soleh, Ahmad; Rahman, Abdul (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2025)
The aim of this research is to determine transformational leadership and self-efficacy on employee performance at the Lebong Regency Regional Secretariat. The sample in this study was 79 employees at the Lebong Regency Regional Secretariat who had become ASN. The sampling technique is census. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The multiple regression results show a positive regression direction with the equation Y = 13.190 + 0.285X1 + 0.421 X2. Transformational leadership has a significant influence on employee performance at the Lebong Regency Regional Secretariat because the significant value of 0.000 is less than 0.05. This illustrates that as transformational leadership increases, employee performance will also increase. Self-efficacy has a significant influence on employee performance at the Lebong Regency Regional Secretariat because the significant value of 0.000 is smaller than 0.05. This illustrates that the more self-efficacy increases, the employee performance will also increase. Transformational leadership and self-efficacy have a significant simultaneous influence on employee performance at the Lebong Regency Regional Secretariat because the significant value of 0.000 is smaller than 0.05.